Mengembangkan Kreativitas dalam Berpikir Melalui Pengaiaran Sains - Adang S., H. Juariah (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 1993)
This article provide{views on different approach in science teaching which candevelop creative thinking in the approach apply (1) system apporach. (21 problemsolving strategy and (3) science process skill approaches and supported by creativeteacher with open heart, not frighten but able to make students find themselves willand able to modify and develop subject matter. By developing, thinking creatively inscience teaching, is hoped that students are able (1) to solve problems usingalternative ways, and (2) to decide causal relation about objects observed.